Comparison of implant related complications amongst patients with opioid use disorder and non-users following total knee arthroplasty - Vakharia, Rushabh M (World J Orthop, 2019)
BACKGROUND: The influence of opioid use disorder on implant related complications, infection and readmission rates, and total global episode-of-care costs following primary total knee arthroplasty (TKA) is limited. AIM: To examine whether opioid abuse in patients undergoing primary TKA. METHODS: A retrospective analysis of the Medicare dataset, using the PearlDiver database, from 2005-2014 comparing outcomes in patients with opioid abusers (OUD) to non-opioid abusers (NOU) undergoing primary TKA was performed. Patient outcomes were analyzed including implant complications, readmission rates, and day-of-surgery and 90-d cost. Statistical analysis was performed with R (University of Auckland, New Zealand) calculating odds-ratio (OR) along with their respective 95% confidence interval (95%CI) and P-values. RESULTS: The OUD group was at greater odds of having implant related complications overall (20.84% vs 11.25%; OR: 2.07; 95%CI: 1.93-2.23; P < 0.001). Revision (OR: 2.07; 95%CI: 1.11-3.84; P < 0.001), infection (OR: 1.92; 95%CI: 1.72–2.18; P < 0.001), periprosthetic fractures (OR: 1.83; 95%CI: 1.16-4.79; P < 0.001), and 90-d readmission rates (OR: 1.47, 95%CI: 1.35-1.61, P < 0.001) were also significantly increased. OUD patients also incurred in higher day-of-surgery and total global 90-d episode-of-care costs compared to NOU. CONCLUSION: Patients with OUD show an increased risk of complications compared to the non-opioid users group. Appropriate recognition, pre-surgical optimization, and patient education are essential to mitigate these complications and improve patient outcome.